Knowledge Management on Teaching Profession According to Khurusapha Content Standards Using Electronic Medias Enhancing e-Learning Knowledgebase - Chongchaikit, Maturos (Ratchaphruek Journal, 2015)
The “Knowledge Management on Teaching Profession According to Khurusapha Content Standards Using Electronic Medias Enhancing e-Learning Knowledgebase” was a master Research project funded in 2012 by Thailand Cyber University Office under the Commission of Higher Education with the following 3 subprojects: “Synthesis of Teaching Profession Learning Contents According to Khurusapha Content Standards for the Electronic Medias Enhancing e-Learning Knowledgebase”; “Development of Learning Objects on Teaching Profession According to Khurusapha Content Standards as Electronic Medias Enhancing e-Learning Knowledgebase” and “The Implementation Study of the Knowledge Management on Teaching Profession According to Kurusapha Content Standards Using Electronic Medias Enhancing e-Learning Knowledgebase”. The objectives of the research were to: 1) analyze and synthesize the knowledge according to 7 Khurusapha Content Standards; 2) design and develop the learning objects on teaching profession according to Khurusapha Content Standards as electronic medias enhancing e-Learning knowledgebase; 3) design and develop the knowledge management system on teaching profession according to Khurusapha Content Standards; and 4) study the effects of the knowledge management on teaching profession according to Khurusapha Content Standards using electronic medias enhancing e-Learning knowledgebase. The two sample groups were selected from Bangkok and Korat provinces for the trial usage of the KMS website, using the multistage sampling. The 1st sample group consisted of 3 subgroups of 5 persons with different educational careers in each. The 2nd sample group was 100 teaching profession students in Nakhon Ratchasima Rajabhat University. The research tools were the questionnaires for the experts and for the sample groups. The findings were as follows: 1) the Knowledge Management System for Teaching Profession according to 7 Khurusapha Content Standards consists of the knowledgebase containing 50 learning objects and the electronic Thai and foreign learning resources supporting Khurusapha Content Standards: educational institutes, educational journal and research, mass media for education ; 2) the KMS website was composed of 3 main parts for the management of the explicit knowledge, the tacit knowledge and the communication channels (LeMill, 2009); 3) the trial usage of the KMS website revealed the satisfaction of the sample group at the high and the highest levels. They had good opinions with its usage as the open knowledge resources for teaching profession according to Khurusapha Content Standards. The solutions used for managing the problems while conducting subprojects could be benefit to further LO and KMS developers both for the content design and for the storyboarding. (Wiley, D.A.,2000 ; Susan E.Metros, 2005; EDUTECH Wiki, 2011) การจัดการความรู้ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาด้วยคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบ อีเลิร์นนิงเป็นแผนงานวิจัยหลักชึ่งได้รับทุนอุดหนุนการดำเนินงานจากโครงการมหาวิทยาลัยไซเบอร์ไทย สำนักงานคณะ กรรมการการอุดมศึกษาประกอบด้วยโครงการวิจัยย่อย 3 โครงการคือ “การสังเคราะห์สาระความรู้ด้านวิชาชีพครู ตามมาตรฐานความรู้คุรุสภาสำหรับคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบอีเลิร์นนิง” “การพัฒนาสื่อการเรียนรู้ดิจิทัล ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาสำหรับคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบอีเลิร์นนิง” และ“การศึกษา ผลการจัดการความรู้ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาด้วยคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบ อีเลิร์นนิง”การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อ 1) วิเคราะห์สังเคราะห์ สาระความรู้ด้านวิชาชีพครูตาม 7 มาตรฐานความรู้ คุรุสภา; 2) ออกแบบและพัฒนาสื่อการเรียนรู้ดิจิตัลสำหรับคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบอีเลิร์นนิง; 3) ออกแบบและพัฒนาระบบการจัดการความรู้ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาและ 4) ศึกษาผลการจัดการ ความรู้ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาด้วยคลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบอีเลิร์นนิงกลุ่มตัวอย่าง 2 กลุ่มซึ่งได้จากการสุ่มแบบหลายขั้นตอนจากจังหวัดกรุงเทพมหานครและโคราชเพื่อลองใช้ระบบการจัดการความรู้ ด้านวิชาชีพครูตามมาตรฐานความรู้คุรุสภาได้แก่ (1) บุคลากรทางการศึกษาด้านวิชาชีพครู 3 กลุ่ม ๆ ละ 5 คนแต่ละกลุ่ม ประกอบด้วยครูอาจารย์นิสิตนักศึกษาวิชาชีพครูศึกษานิเทศก์และผู้บริหารสถานศึกษาและ (2) นักศึกษาวิชาชีพครู ระดับปริญญาตรี ในมหาวิทยาลัยราชภัฏนครราชสีมาจำนวน 100 คนเครื่องมือวิจัยได้แก่แบบสอบถามสำหรับผู้ทรงคุณวุฒิ และกลุ่มตัวอย่าง ผลการวิจัยพบว่า 1) ระบบการจัดการความรู้ด้านวิชาชีพครูบรรจุส่วนการจัดการความรู้ชัดแจ้ง คือ คลังสื่ออิเล็กทรอนิกส์ส่งเสริมการเรียนรู้แบบอีเลิร์นนิงประกอบด้วยสื่อการเรียนรู้ดิจิตัลตามมาตรฐานความรู้คุรุสภา 7 มาตรฐาน จำนวน 50 บทเรียน และแหล่งทรัพยากรการเรียนรู้ที่สนับสนุนการพัฒนาสมรรถนะตามมาตรฐานวิชาชีพครู ได้แก่เว็บไซต์หน่วยงานทางการศึกษาวารสารทางการศึกษาและการวิจัยสื่อมวลชนเพื่อการศึกษา; 2) เว็บไซต์ระบบการ จัดการความรู้ฯ ประกอบด้วย 3 ส่วนหลัก คือส่วนจัดการความรู้ชัดแจ้ง ส่วนจัดการความรู้หยั่งลึกและส่วนช่องทางติดต่อ สื่อสาร (LeMill, 2009) ; 3) จากผลการลองใช้พบว่า กลุ่มตัวอย่างผู้ใช้ส่วนใหญ่มีความพึงพอใจในระดับมากถึงมากที่สุดมี ความคิดเห็นเชิงบวกต่อความสอดคล้องกับมาตรฐานความรู้คุรุสภาของระบบการจัดการความรู้ฯ และต่อลักษณะของ คลังความรู้แบบเปดิ สำหรับการพัฒนาวิชาชีพครูตามมาตรฐานความรู้ของคุรุสภาองค์ความรู้ที่เกิดขึ้นจากการแก้ไขปัญหา ในการดำเนินงานวิจัย สามารถเป็นประโยชน์ต่อผู้ที่ต้องการพัฒนาสื่อการเรียนรู้ดิจิทัล(LO)และระบบการจัดการความรู้ (KMS) ทั้งในส่วนของการพัฒนาเนื้อหา และการพัฒนาสตอรี่บอร์ด (Wiley, D.A., 2000 ; Susan E.Metros, 2005; EDUTECH Wiki, 2011)